PENGARUH KELEMBABAN TANAH TERHADAP TAHANAN PENTANAHAN STUDI KASUS PADA GARDU INDUK KEMAYORAN 150 kV - Rahmawati Fajri Latiefa; Irzan Zakir; Massus Subekti (Journal of Electrical Vocational Education and Technology, 2018)
Abstract The value of grounding resistance at the substation should be 0 Ω or less than 1 Ω. The value of grounding resistance is influenced by the resistivity and the grounding system method used. the resistivity is influenced by external factors, one of which is the soil moisture. The purpose of this research are (i) to find the effect of soil moisture to grounding resistance with; (a) compare the actual measurements of grounding resistance between wet soil conditions and dry soil conditions; (b) compare actual measurement results, manual calculations, and ETAP 12.6 software on grid resistance between wet soil conditions and dry soil conditions. (ii) to find the effect that would occur if the grounding station resistance exceeds the IEEE Std 80-2000 standard value of less than 1 Ω. The research method is comparative quantitative. This research is measuring grounding resistance with driven rood system and with grid system during wet and dry soil conditions, and then calculate grid resistance of Kemayoran 150 kV Substation in dry and wet soil conditions using manual calculating based on IEEE Std 80 -2000, and calculating using ETAP 12.6 software. The result of measument grounding resistance with driven rood system show the value of grounding resistance is 27,72 Ω when dry soil condition and 18,92 Ω when wet soil condition, the measurement result of grounding resistance with grid system show the value of grounding resistance is 0.076 Ω when the soil condition is dry and 0.049 Ω during wet soil conditions, the manual calculation of grid resistance is 0.078 Ω for dry soil conditions and 0.056 Ω, and the ETAP calculation of grid resistance is 0.071 Ω for dry soil conditions and 0.051 Ω for wet soil conditions. Based on the results of this research, the conclusion is soil moisture can affect the value of grounding resistance, based on this research the dry soil condition of the earth resistance value is higher than the wet soil conditions. The value of earthquake grounding shall be less than 1 Ω due to minimize the earth potenial value (Ground Potensial Rise) which can cause dangerous voltage for humans. Abstrak Nilai tahanan pentaahan pada Gardu Induk harus mendekati 0 Ω atau kurang dari 1 Ω, dan dipengaruhi oleh tahanan jenis tanah dan metode sistem pentanahan yang digunakan. Tahanan jenis tanah dipengaruhi oleh faktor eksternal, salah satunya adanya kelembaban tanah. Tujuan dari penelitian ini adalah mengetahui pengaruh kelembaban tanah terhadap nilai tahanan pentanahan, dan mengetahui pengaruh yang akan terjadi jika tahanana pentanahan gardu induk melebihi nilai standar IEEE Std 80-2000 yaitu kurang dari 1 Ω. Penelitian ini melakukan pengukuran aktual tahanan pentanahan dengan sistem driven rood dan tahanan pentanahan dengan sistem grid saat kondisi tanah basah dan tanah kering, serta perhitungan tahanan pentanhan grid Gardu Induk Kemayoran 150 kV dalam kondisi tanah kering dan tanah basah dengan menggunakan perhitungan manual berdasarkan IEEE Std 80-2000, dan perhitungan menggunakan software ETAP 12.6. Dalam penelitian ini ditemukan bahwa kelembaban tanah dapat mempengaruhi nilai tahanan pentanahan, dengan berdasarkan saat kondisi tanah kering nilai tahanan pentanahan lebih tinggi dibandingkan saat kondisi tanah basah Hasil pengukuran tahanan pentanahan dengan sistem driven rood menunjukkan nilai tahanan pentanahan adalah 27,72 Ω saat kondisi tanah kering dan 18,92 Ω saat kondisi tanah basah, hasil pengukuran tahanan pentanahan dengan sistem grid menunjukkan nilai tahanan pentanahan adalah 0,076 Ω saat kondisi tanah kering dan 0,049 Ω saat kondisi tanah basah, hasil perhitungan manual tahanan grid adalah 0,078 Ω untuk kondisi tanah kering dan 0,056 Ω, dan hasil perhitungan ETAP tahanan grid adalah 0,071 Ω untuk kondisi tanah kering dan 0,051 Ω untuk kondisi tanah basah.